Managing urban mobility systems - Macário, Rosário (Emerald Group Pub., 2011)
"Urban mobility is currently a major problem all over the world. Space is limited, and individuals aim for a level of quality in mobility that is only achieved by largely motorised solutions, which have a detrimental effect on the urban environment. Careful analysis of urban mobility systems across the world reveals that consistent and effective policies can only be defined and implemented if the various components of the system and their interrelations are considered. This book addresses the problem of managing urban mobility systems in a novel way by considering the complexity and diversity of the conurbation and agents involved in a UMS, putting forward the evidence that urban mobility must be managed at system level."--Publisher's site.
Keywords: Urban transportation policy.; Urban transportation -- Planning.; elektronické knihy; electronic books